Potensi Geodiversity Daerah Oluhuta Kecamatan Kabila Bone Kabupaten Bone Bolango Menggunakan Asesmen - Ponto, Nadia Fransisca; Arifin, Yayu Indriati; Hutagalung, Ronal; Akase, Noviar; Manyoe, Intan Noviantari (Universitas Negeri Gorontalo, 2023)
Geotourism emphasizes the beauty, uniqueness, rarity and wonder of natural phenomena as an impetus for the development of geology-based tourism. The many variations in geological aspects fulfill the potential geodiversity value in the area. The aim of this research is to identify and assess the potential for geodiversity in Oluhuta Village. The research location has coordinates 0° 25' 0